Molecular Magnets: The Synthesis and Characterization of High‐Spin Nitrenes. Issue 4 (5th November 2020) - Chapyshev, Sergei V.; Mendez‐Vega, Enrique; Sander, Wolfram
Abstract: Among all C‐, N‐, and O‐centered polyradicals, high‐spin nitrenes possess the largest magnetic anisotropy and are of considerable interest as multi‐level molecular spin systems for exploration of organic molecular magnetism and quantum information processing. Although the first representatives of quintet and septet nitrenes were obtained almost 50 years ago, the experimental and theoretical studies of these highly reactive species became possible only recently, owing to new achievements in molecular spectroscopy and computational chemistry. Meanwhile, dozens of various quintet dinitrenes and septet trinitrenes were successfully characterized by IR, UV/Vis, and EPR spectroscopy, thus providing important information about the electronic structure, magnetic properties and reactivity of these compounds. Abstract : Mega‐magnets : High‐spin nitrenes exhibit the strongest magnetic properties among organic polyradicals, emerging as promising building blocks for the design of organic magnetic materials. This Minireview focuses on ferromagnetically coupled aryl di‐ and trinitrenes, covering from quintet to septet spin states. Synthesis, spectroscopy, magnetic properties, and electronic structure of these paramagnetic species is discussed herein.